Sediment toxicity identification evaluation (TIE phases I and II) based on microscale bioassays for diagnosing causes of toxicity in coastal areas affected by domestic sewage - Ferraz, Mariana Aliceda; Alves, Aline Vecchio; de Cássia Muniz, Cynthia; Pusceddu, Fabio Hermes; Gusso-Choueri, Paloma Kachel [UNESP]; Santos, Aldo Ramos; Choueri, Rodrigo Brasil (Oxford University Press (OUP), 2017)
Domestic sewage is a major problem in highly urbanized coastal areas worldwide. In the present study, toxicity identification evaluation (TIE) phases I and II were applied to sediment interstitial water from 2 locations along the São Paulo coast in southeastern Brazil: the sewage outfalls from the city of Santos, a densely urbanized area, and the city of Bertioga, a less urbanized area. An adapted microscale sea urchin embryo–larval development bioassay was employed. Phase TIE-I manipulations were 1) ethylenediamine tetraacetic acid (EDTA) addition, 2) aeration at modified pH, 3) C18 solid-phase extraction (SPE), and 4) addition of Na2S2O3. The results of the Santos TIE-I indicated toxicity by sulfides and substances with affinity to C18 resin. In Bertioga, toxicity was the result of NH3, metals, and arsenic, as well as substances with affinity to C18 resin. Phase TIE-II aimed to specify the causes of toxicity by testing the toxicity of eluates of the sublation and C18 SPE manipulation. The results reinforced the role of both surfactants and nonpolar compounds as causative agents of toxicity in both Santos and Bertioga. Chemical analyses of sediment interstitial water or whole sediment ruled out the influence of polycyclic aromatic hydrocarbons (PAHs) or polychlorinated biphenyls (PCBs) in the toxicity of both sampling sites. Other hydrophobic substances may play a role in the toxicity of Santos and Bertioga effluents. Efforts to remove such substances from sanitary effluents must be prioritized. Environ Toxicol Chem 2017;36:1820–1832. © 2017 SETAC.
Keywords: Municipal effluents; Sea urchin; Sediment assessment; Sediment porewater; Toxic identification evaluation; Toxicant identification